Foods, Fuels or Finances: Which Prices Matter for Biofuels? - Ondrej Filip; Karel Janda; Ladislav Kristoufek; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We examine co-movements between biofuels (ethanol and biodiesel) and a wide range of commodities and assets in the USA, Europe, and Brazil. The main contributions are twofold. First, we analyze a unique dataset of 32 commodities and relevant assets (between 2003 and 2015) which is unprecedented in the biofuels literature. And second, we combine the minimum spanning trees correlation filtration to detect the most important connections of the broad analyzed system with continuous wavelet analysis which allows for studying dynamic connections between biofuels and relevant commodities and assets and their frequency characteristics as well. We confirm that for the Brazilian and US ethanol, their respective feedstock commodities lead the prices of biofuels, and not vice versa. This dynamics remains qualitatively unchanged when controlling for the influence of crude oil prices. As opposed to the Brazilian and US ethanol, European biodiesel exhibits only moderate ties to its production factors.
Keywords: C22; C38; Q16; Q42; 330; biofuels; prices; minimum spanning tree; wavelet coherenc